PERANCANGAN RENDER FARM ANIMASI DENGAN BLENDER PADA UBUNTU (Information Technology and Telematics, 2014)
Rendering is a process to change themodel geometry into an image. To render the processusually takes a long time, especially for rendering imagesof photo-realistic. To overcome the problem, renderingfarm can be used as an alternative option.Rendering farm is a set of computers that worktogether to do the same rendering process . Thereisseveral tools or software that can be used to built arendering farm.Loki-Render is one of the tools that can be used tobuild a rendering farm. Loki-Render will be very efectivewhen used for animation rendering, Loki-Render will splitand distribute the frame of the animation to eachcomputer. The process of splitting the frame is donemanually by the user, using ssh to connect on each clientcomputer.Keywords: Render Farm, Rendering, Animation,blender